2020
DOI: 10.1021/acsami.0c12073
|View full text |Cite
|
Sign up to set email alerts
|

Residual Compressive Stress Enabled 2D-to-3D Junction Transformation in Amorphous Carbon Films for Stretchable Strain Sensors

Abstract: Usually, two-dimensional (2D) flexible strain sensors based on cracks have very high sensitivities but small measuring ranges, while the three-dimensional (3D) ones behave in the opposite way. Here, by utilizing the large residual compressive stress of an amorphous carbon (a-C) film and the flexibility of polydimethylsiloxane (PDMS), we developed a facile and economic strategy to fabricate a high-sensitive a-C/PDMS stretchable strain sensor. Results showed that for the first time, the a-C film ranging from 25 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Furthermore, this sensor could transmit the sensing data of volunteers in real time through a big data cloud platform at a distance of 62 km. In 2020, Wang et al [121] described a 2D-to-3D electrical junction transformation strategy for fabricating sensitive stretchable strain sensors based on the release of high residual compressive stress and the large difference in Young's modulus of the a-C/hardened PDMS/PDMS multilayer system. Using this strategy to achieve cracks, wrinkles, and 3D junctions, they increased the sensitivity to a GF of 746.7, the strain sensor range up to 0.5, and repeatability over 5000 cycles.…”
Section: Strain Sensorsmentioning
confidence: 99%
“…Furthermore, this sensor could transmit the sensing data of volunteers in real time through a big data cloud platform at a distance of 62 km. In 2020, Wang et al [121] described a 2D-to-3D electrical junction transformation strategy for fabricating sensitive stretchable strain sensors based on the release of high residual compressive stress and the large difference in Young's modulus of the a-C/hardened PDMS/PDMS multilayer system. Using this strategy to achieve cracks, wrinkles, and 3D junctions, they increased the sensitivity to a GF of 746.7, the strain sensor range up to 0.5, and repeatability over 5000 cycles.…”
Section: Strain Sensorsmentioning
confidence: 99%
“…This section proposes potential practical applications of the a-C thin films on the basis of corresponding recent achievements. The applications in which the a-C thin films can function by themselves such as hardmask, [102][103][104][105] EUV pellicle, [106] and diffusion barrier [38,66,107,108] are discussed first, and the applications as a system of the device are followed, including deformable electrodes and interconnections, [14,15,109] sensors, [110][111][112][113][114][115][116][117][118][119][120][121][122][123] active channel layers, [124] electrodes for energy devices, [125,126] micro-supercapacitors, [125,127,128] batteries, [43,129] nanogenerators, [44,126] EMI shielding, [41] and nanomembranes. [128][129][130]…”
Section: Potential Industrial Applicationsmentioning
confidence: 99%
“…Results showed that, for the first time, the a-C film ranging from 25 nm to 1 µm changed the shape and orientation of conductive scales, and especially, the sensor with a 1 µm thick a-C film provided a maximum gauge factor of 746.7 and strain range up to 0.5. [131] a-C and its carbon-containing variant, i.e., tetrahedral amorphous carbon (ta-C), have also garnered significant attention for their uses as electrodes [132,133] owing to their large water window [134] and low background signal. [135] According to the literature, carbon thin film electrodes have been used for the selective determination of dopamine concentrations [135] as sensors, and moreover, a-C thin films with intrinsic platinum gradients have been employed as electrodes for electrochemical detection of hydrogen peroxide.…”
Section: Conductive Materialsmentioning
confidence: 99%